(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The study approaches the recent production of Brazilian theater, based on the plays of the festival Verão Sem Censura (2020), in order to map traces of Decoloniality that seem to impose themselves in the broader panorama. It proposes, then, as a creative gesture regarding this scene that has been challenging and confronting basic principles of theater, the emergence of the word/concept Teatre, giving a history of its socio-cultural antecedents and observing its poetic-political modes of action.